2022
DOI: 10.2196/42320
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of the First UK COVID-19 Lockdown on Users of the Drink Less App: Interrupted Time Series Analysis of Sociodemographic Characteristics, Engagement, and Alcohol Reduction

Abstract: Background The first UK COVID-19 lockdown had a polarizing impact on drinking behavior and may have impacted engagement with digital interventions to reduce alcohol consumption. Objective We examined the effect of lockdown on engagement, alcohol reduction, and the sociodemographic characteristics of users of the popular and widely available alcohol reduction app Drink Less. Methods This was a natural experim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 35 publications
0
2
0
Order By: Relevance
“…The marked increase in sales between first and second quarter of 2020 for alcohol in all three countries may largely reflect pre-pandemic seasonality. Some cross-sectional surveys from other countries, such as Germany (Koopmann et al, 2021), the UK (Oldham et al, 2022) and the US (Barbosa et al, 2021; Castaldelli-Maia et al, 2021) also reported an increase of drinking during spring 2020. These surveys, may, to a degree, have picked up similar seasonal effects.…”
Section: Discussionmentioning
confidence: 99%
“…The marked increase in sales between first and second quarter of 2020 for alcohol in all three countries may largely reflect pre-pandemic seasonality. Some cross-sectional surveys from other countries, such as Germany (Koopmann et al, 2021), the UK (Oldham et al, 2022) and the US (Barbosa et al, 2021; Castaldelli-Maia et al, 2021) also reported an increase of drinking during spring 2020. These surveys, may, to a degree, have picked up similar seasonal effects.…”
Section: Discussionmentioning
confidence: 99%
“…Compared with traditional autoregressive integrated moving average models, GAMM allow a more flexible modelling of seasonality and control for external confounders. Accordingly, GAMM are increasingly used to evaluate the impact of the COVID-19 pandemic 19 or alcohol control policies. 20 The model selection is described in the Supplementary material .…”
Section: Methodsmentioning
confidence: 99%